KONSEP PENDIDIKAN AKHLAK BAGI PESERTA DIDIK DALAM PERSPEKTIF SYEKH ABDUL QADIR AL-JAILANI - Ahmad Rafi Al Hazmi (MUMTAZ : Jurnal Pendidikan Agama Islam, 2023)
The aims of this study are: (1) to find out how the moral education for students according to Sheikh Abdul Qadir al-Jailani. (2) to determine the relevance of moral education for students according to Sheikh Abdul Qadir al-Jailani with the context of today's education. The research method used is a qualitative research method with a library research approach which requires books, journals, other research, and other literature related to the title of this study which is the source of data in this study, to test this research using data reduction testing. , data presentation, and conclusion drawing/verificatio. The moral education taught by Sheikh Abdul Qadir al-Jailani that students must have the will, the goal, the right belief, be honest in earnest, sincere to Allah SWT, should not be proud of themselves, should not underestimate something and be stingy, be pleased with what is taught by the teacher, leaving the debate with the teacher, not suudzon and indulgence in the teacher's disgrace, introspection when the teacher is angry, etiquette to speak and listen to the teacher, believe in the teacher, learn with pleasure.